Woman and Human Rights in Nigeria: A Study of Delta State - UDJOH, Purity (International Journal of Public Administration Studies, 2024)
The Constitution of the Federal Republic of Nigeria 1999 chose certain rights to protect under chapter IV and termed them as Fundamental Rights. These rights protected not only by the Constitution, but also by the African Charter on Human and Peoples Right. Whenever there are breaches of these fundamental rights, the law provides a procedure for their enforcement, which is the Fundamental Rights (Enforcement Procedure) Rules 2009. The basic objective of the 2009 Rules is to facilitate enforcement procedure by removing some of the impediments in 1979 rule. Unfortunately, it is clear that the procedure for enforcement of Fundamental Rights is still bedeviled by delay. Many applications alleging serious human rights violations are routinely struck out or dismissed. However, the pertinent question is: to what extent are the human rights provision in these legal instruments realized or enforced as it relates to the women folk? It is worthy of note that there are equally other important impediments in the realization of the objective of Fundamental Rights (Enforcement Procedure) Rules 2009, such as the distinction between main claim and ancillary claim in the Nigerian fundamental rights, because litigants are cautious of whether or not their will succeed because of this distinction. This research examines Women and Human Rights in Nigeria. This research made an in depth analysis of the rules and considered to what extent it achieved its objective in order to enhance a robust human right regime as it relates to the women folk. To achieve a close -to- accurate" if not accurate result, the research embarked on a field work. To this end, empirical method of research is used. This research found out that the Fundamental Rights (Enforcement Procedure) Rules 2009, though has brought tremendous changes in the field of human rights protection (e.g the abolishment of locus standi and leave, is still faced with some major setback like the issue of principal and ancillary claim in the enforcement of fundamental rights and the jurisdiction of the National Industrial Court which is not clear in the rule. The work recommend that Courts should do away with the dichotomy between principal and ancillary and the definition of courts in the Rule should include the National Industrial Court.